الحداثة البديلة بين طه عبد الرحمن وبديع الزمان النورسي: دراسة وصفية مقارنة: Alternative Modernity Between Taha Abdurrahman and Bediüzzaman Said Nursi: A Comparative Descriptive Study - Abo Ayash, Sameer; Saged, Ali Ali Gobaili; Zainal Abidin, Azmil (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
This study explores the concept of ‘alternative modernity’ in Islam, focusing on principles and approaches that Muslims can adopt to develop it and offering a contemporary perspective on Islamic thought. It addresses the challenge posed by Western modernity, which has significantly impacted the Muslim world by promoting the liberation of individuals from restrictions and overemphasizing rationality and humanization, conflicting with Islamic revelation. This has created a need for an alternative modernity that aligns with Islamic values. The study examines whether it can modify Western modernity into an Islamic version based on ethics and values. It focuses on the contributions of two thinkers, Taha Abdurrahman and Bediüzzaman Said Nursi, who attempt to provide an alternative modernity suited to the Arab and Islamic worlds by adapting Western modernity while preserving Islamic heritage. This research highlights the importance of critiquing Western modernity. It emphasizes the possibility of creating an alternative that integrates Islamic principles, rejecting rationalism alone and fostering a deeper connection with heritage. The study concludes that Muslim thinkers can critically engage with Western modernity, identifying its risks to Islamic societies and proposing an alternative that rectifies its shortcomings by re-engaging with heritage. By adopting a descriptive and analytical approach, this research aims to demonstrate how Taha’s Western modernity and Nursi’s ideas contribute to developing an Islamic alternative modernity for the Muslim world.